Meningkatkan Kedisiplinan Siswa Melalui Pengelolaan Kelas di SDN 23 Pagi Palmerah Jakart - Aulia Rachman; Murniati Agustian (Universitas Katolik Indonesia Atma Jaya, 2016)
This study is a classroom action research that aims to improve the students’ discipline by implementing effective classroom management. Discipline is an attitude to obey the order through training, supervision, and habituation. It is created in order, for individuals, to be obedient in school. Classroom management is the effort, in terms of activities, performed teachers, deliberately, to create and to maintain conducive learning situations, to enhance meaningful learning activities (active, effective, efficient, enjoyable), and to reduce boredom. The participants were the fourth grade students of SDN 23 Pagi Palmerah. The research result reported that the students’ discipline was significantly improved. It was proved by the improvement of the level of discipline from 70.75% to 83.49%. It can be inferred that the level of discipline of students can be improved by implementation of effective classroom management.